2020
DOI: 10.1002/cam4.2832
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking increases the risk of nasopharyngeal carcinoma through the elevated level of IgA antibody against Epstein‐Barr virus capsid antigen: A mediation analysis

Abstract: Background The study aims are to evaluate the associations between nasopharyngeal carcinoma (NPC) risk and cigarette smoking and to explore the effects of cigarette smoking on Epstein‐Barr virus (EBV) infection for NPC risk. Methods 1235 male NPC cases and 1262 hospital‐based male controls matched to cases were recruited across six collaborative hospitals between 2010 and 2014. Using a standardized questionnaire, information on cigarette smoking and other potential risk factors for NPC was obtained. Blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…One possibility is that the association between smoking and NPC was mediated through Epstein-Barr virus (EBV) reactivation. 34 , 58 , 59 EBV is closely associated with the occurrence and development of NPC, and its reactivation is associated with smoking. Whereas one study in subjects with elevated IgA antibodies against EBV viral capsid antigen (VCA/IgA) found a null association between smoking and EBV, 60 several large studies in healthy subjects showed that both smoking 61 , 62 and cotinine 63 were associated with higher seropositivity for several biomarkers of EBV reactivation and subsequently with higher risk of NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the association between smoking and NPC was mediated through Epstein-Barr virus (EBV) reactivation. 34 , 58 , 59 EBV is closely associated with the occurrence and development of NPC, and its reactivation is associated with smoking. Whereas one study in subjects with elevated IgA antibodies against EBV viral capsid antigen (VCA/IgA) found a null association between smoking and EBV, 60 several large studies in healthy subjects showed that both smoking 61 , 62 and cotinine 63 were associated with higher seropositivity for several biomarkers of EBV reactivation and subsequently with higher risk of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas one study in subjects with elevated IgA antibodies against EBV viral capsid antigen (VCA/IgA) found a null association between smoking and EBV, 60 several large studies in healthy subjects showed that both smoking 61 , 62 and cotinine 63 were associated with higher seropositivity for several biomarkers of EBV reactivation and subsequently with higher risk of NPC. 34 , 59 Another possibility is formaldehyde, a constituent of cigarette smoke which causes squamous cell carcinoma of the nasal cavities upon inhalation exposure of rats, and formaldehyde is considered a cause of nasopharyngeal cancer in humans by IARC. 64 A study demonstrated a 10-fold higher level of the formaldehyde-DNA adduct N6-hydroxymethyl deoxyadenosine in leukocytes of smokers than never smokers, suggesting its possible involvement in NPC in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Although tobacco smoking is more strongly associated with type I squamous cell than types II and III nonkeratinizing NPC, several studies in high-incidence regions, where the vast majority of NPC is nonkeratinizing, also demonstrate a modestly increased risk of NPC associated with tobacco smoking, with two meta-analyses of more than 20 studies showing an approximately 60% greater risk among ever than never smokers (54,55). Smoking may increase NPC risk in part through reactivation of latent EBV infection, as suggested by studies that reported positive associations between cigarette smoking and elevated levels of anti-EBV IgA antibodies among subjects without NPC (56)(57)(58).…”
Section: Tobacco and Other Smokementioning
confidence: 99%
“…In 2004 and 2012, the International Agency for Research on Cancer reported that cigarette smoking increases NPC risk in both endemic and nonendemic regions ( 10 , 11 ), while the Health Consequences of Smoking Report by the US Surgeon General in 2014 only concluded on the carcinogenicity for oropharynx but not for nasopharynx due to insufficient evidence ( 12 ). After that, further evidence has emerged ( 1 , 13 16 ) and a meta-analysis showed that every 10 more pack-years of smoking was associated with 15% higher risk of NPC ( 17 ). Our recent individual data meta-analysis of cohort studies in endemic regions has also provided strong evidence for a causal relation between smoking and NPC ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another large case-control study (1,857 NPC cases and 1,907 community controls) in Guangdong and Guangxi, southern China showed that compared with never smokers, NPC risk was lower for short-term quitters (quitting for ≤9 years; AOR: 0.54; 95% CI: 0.39–0.75) but higher for long-term quitters (≥10 years; 1.44, 1.04–2.00) ( 15 ). The latest case-control study in Taiwan reported that, compared with never smoking, quitting for ≤5 years was associated with a higher NPC risk (1.54, 1.04–2.29), and quitting for ≥6 years showed no association (1.02, 0.67–1.56 for 6–10 years; 1.25, 0.93–1.69 for >10 years) ( 16 ). We have found no reports on NPC risk by age at quitting and smoking duration as of July 2021.…”
Section: Introductionmentioning
confidence: 99%